Rural Religions in Late Antiquity: Changing the Rules of the Game - Alvar Nuño, Antón; Martínez Maza, Clelia (ARYS. Antigüedad: Religiones y Sociedades, 2021)
Up until recently, the study of rural religiosity in Late Antiquity has been considered of secondary importance among specialists; it has been centred either on the study of pagan survivals in the rural landscape, or on the spread of Christianity by the main power structures. Our intention in this paper is to open up the scope of analysis by focusing on the rural world’s own idiosyncrasy, the importance of space morphology and the variety of agents who dynamically interact in rural landscapes, leaving aside the idea of considering rural agents and rural space as passive receivers of new religious models. To do so, our methodology prioritises the study of religious motivations in the rich social spectrum of the rural world by considering not just the capacity of potentes and domini to exert influence on the local religious options, but by considering also the partaking of the whole range of small landowners, tenants, day laborers and slaves that inhabited the rural world. As we focus on the dynamism of rural religious experiences and how the space has an impact in the configuration of religious systems, we expect to enrich the current debate, including in it the ways in which individual religious motivations and expectations – conditioned by spatial and socio-economic factors – intervene and modify the local religious map.
Keywords: Christianism; cultural landscapes; Late Antique Polytheism; rural religions; rural world